Bones never lie : how forensics helps solve history's mysteries - MacLeod, Elizabeth (Annick Press, 2013)
Uses forensic sciences to try to solve some of the world's mysteries, including how Napoleon died, the identity of the Man in the Iron Mask, and the fate of Thailand's King Rama.